Acupuncture analgesia: The complementary pain management in dentistry - Abdurachman Abdurachman (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Pain is the most common reason for medical consultation in the United States. Pain is a major symptom in many medical conditions, and can significantly interfere with a person’s quality of life and general functioning. One of the very unpleasant pain is toothache. Conventional treatments for toothache are improving oral hygiene, prescribing analgesics, anti-inflammatory, and also antibiotics if there are infection even extractions are performed if necessary. Another way to conventional approaches, patients may consider acupuncture method. Acupuncture involves the insertion of needles with the width of a human hair along the precise points throughout the body. This process triggers body’s energy normal flow through extra anatomy pathway called meridian. Purpose: This case report is aimed to emphasize the existence of teeth-organ relationships through communication channels outside the lines of communication that has been known in anatomy. Case: Two patients with toothache complaints in the lower right molars came to an acupuncturist who was a medical practitioner. In these cases pain were relieved by acupuncture analgesia. Case management: Two patients were subjected to acupuncture analgesia with different acupuncture points that were customized to the affected tooth, case 1 with the large intestine-4 (Li-4) which located in the hand and case 2 with bladder-25 (Bl-25) which located in the back of the body. Ninety percent of pain was relieved in 40 seconds. Conclusion: Pain in toothache can be relieved using acupuncture analgesia technique, using meridian as an extra anatomy pathway. Nevertheless, treating the source of pain by dental practitioner is mandatory.Latar belakang: Nyeri adalah alasan paling umum yang menyebabkan orang datang berkonsultasi kepada profesional medis di Amerika Serikat. Nyeri merupakan gejala utama dalam kasus medis, dan dapat mengganggu kualitas hidup dan kegiatan umum seseorang secara signifikan. Salah satu nyeri yang sangat tidak menyenangkan adalah nyeri gigi. Pengobatan selalu diarahkan kepada menjaga kebersihan mulut, memberikan analgesik, mengurangi inflamasi dan menambahkan antibiotik jika ada infeksi bahkan jika perlu dilakukan ekstraksi gigi. Cara lain dari pendekatan konvensional di atas adalah pasien dapat mempertimbangkan metode akupunktur. Akupunktur dilakukan dengan menusukkan jarum seukuran rambut manusia di sepanjang titik yang tepat di seluruh tubuh. Proses ini memicu aliran normal energi tubuh melalui jalur ekstra anatomi disebut meridian. Tujuan: Laporan kasus ini untuk menekankan adanya hubungan gigi-organ melalui jalur komunikasi di luar jalur komunikasi yang telah dikenal dalam anatomi. Kasus: Dua penderita dengan keluhan nyeri gigi geraham kanan bawah dilakukan terapi analgesia akupunktur oleh akupunkturis yang adalah dokter umum. Dalam kasus ini ditunjukkan bahwa rasa nyeri pada gigi dapat dihilangkan menggunakan teknik akupunktur. Tatalaksana kasus: Pasien dengan keluhan nyeri gigi, kasus #1 pada rahang bawah dilakukan terapi akupunktur pada titik Li-4 pada tangan dan kasus #2 pada titik Bl-25 pada pinggang. Pemilihan titik disesuaikan dengan keluhan pasien, menurut teori meridian dalam akupunktur. Nyeri berkurang sampai 90% dalam 40 detik. Kesimpulan: Keluhan nyeri pada gigi dapat dihilangkan menggunakan teknik akupunktur analgesia, menggunakan meridian sebagai jalur komunikasi di luar jalur komunikasi anatomi. Walaupun demikian perawatan kedokteran gigi pada penyebab nyeri yang utama adalah yang paling penting.